Exploring the Impacts of Lead Farmer Selection on Community Social Learning: The case of Farmer-to-Farmer Model: A Review of Literature - Willis Ochieng; Colby J Silvert; John Diaz (Journal of International Agricultural and Extension Education, 2022)
Agricultural extension has shifted towards community-centric, farmer-centered, and participatory approaches that enhance rural change through a social learning lens, resulting in the emergence of the farmer-to-farmer extension model. The purpose of the study was to understand lead farmer selection criteria within the farmer-to-farmer model and their impacts on community social learning. We applied Torraco’s (2005) integrative literature review method to guide our discussion around lead farmer selection processes, types of lead farmers selected and their impacts on social learning. The study indicated farmer-to-farmer extension model has the potential of re-invigorating the provision of agriculture extension services owing to its low cost, reliability, and the potential to be sustainable. However, farmer-to-farmer faces numerous challenges such as a lack of funding, limited community adoption, and acceptance of the system. This study’s findings suggest the farmer-to-farmer approach can be more effective when stakeholders, especially the community is actively involved in designing, implementing, and evaluating the model. The study recommends that practitioners work closely with the community to develop long-term relationships based on trust through intentionality and inviting attitude that respects and values community knowledge.
Keywords: Lead farmer selection; extension effectiveness; farmer-to-farmer; social learning; community perception